HUBUNGAN KUALITAS TIDUR, KONSUMSI NATRIUM DAN LEMAK DENGAN KEJADIAN HIPERTENSI PADA LANSIA DI WILAYAH KERJA PUSKESMAS BATU AJI KOTA BATAM - Khoeriyah, Anisatul; Suntara, Ditte Ayu; Febrina, Trisya Yona (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The incidence of hypertension is one of the number one causes of death globally which requires good control. WHO estimates the global prevalence of hypertension at 22%, in Indonesia the prevalence of hypertension in the elderly is 55.2% at the age of 55-41, 63, 2% at the age of 64-72 years and above. The incidence of hypertension in the city of batam was 42,496 cases. The incidence of hypertension is caused by several factors, one of which is sleep quality, sodium and fat consumption. This study aims to determine the relationship between sleep quality, sodium and fat consumption with the incidence of hypertension in the elderly in the Batu Aji Health Center Working Area, Batam City in 2023. This research design uses cross sectional. This study was conducted on elderly people aged more than 60 years and amounted to 67 samples. The sampling technique used probability sampling, namely random sampling. The results of the Chi-Square Test test obtained the value of sleep quality ((p value) = (0.002 < 0.05), sodium consumption (p value) = (0.004 < 0.05), fat consumption (p value) = (0.001 < 0.05). The conclusion of this study is that there is a relationship between sleep quality, sodium and fat consumption with the incidence of hypertrension in the elderly. The results of this study can be used as knowledge for the elderly to avoid precipitating factors of hypertension, especially sleep quality and avoid consumption of foods containing sodium and fat.